Correlation of B-Type Natriuretic Peptide Level with Severity of Coronary Artery Disease in Non St Elevated Acute Coronary Syndrome with Normal Left Ventricular Function - Mahmud, Sohel; Rahman, AKM Fazlur; Habib, SM Ahsan; Ahmed, Chaudhury Meshkat; Zaman, SM Mustafa; Haque, Mollah Emdadul; Siddika, Khander Aisha; Das, Hironmoy; Ahasan, Md Shamim; Hossain, Md Arif; Hossain, Mohammad Zakir (University Heart Journal, 2017)
Background: Coronary artery disease (CAD) is predicted to be the most common cause of death and disability globally by 2020. In Bangladesh, for better management of coronary artery disease and to reduce the burden of acute coronary events patients with non ST elevated acute coronary syndrome (NSTEACS) should be focused. B-type natriuretic peptide (BNP) can be suggested as a tool to predict severity of coronary atherosclerotic lesion even with normal left ventricular (LV) function and thus to categorize the patients for appropriate referral and invasive evaluation. Aims: This study is designed to assess the relationship between level of BNP and severity of coronary artery disease assessed with SYNTAX score in NSTE-ACS patients with normal LV function. Methods: This cross sectional observational study was conducted at UCC, BSMMU during the period of May 2014 to April 2015 among the patients with non ST elevated myocardial infarction (NSTEMI) and unstable angina. 116 patients were enrolled by non-random purposive sampling who was admitted for coronary angiogram. All the data were recorded in structured questionnaire including details of medical history, coronary risk factors and physical findings. In NSTE-ACS patients with normal LV function venous blood samples were collected for BNP and later SYNTAX scoring was assessed during coronary angiogram. The relationship between level of BNP and SYNTAX score in patients with both UA and NSTE-MI was assessed statistically to evaluate the validity of BNP as a tool to predict severity of coronary atherosclerotic lesions among the patients with NSTE-ACS. Results: The mean age was 57.84±8.82 years. Among the 116 patients, highest frequency of patients was in the age group 51-60 years 55(47.4%) .In which 88(75.9%) were male. Male:Female ratio is 3.1:1.The percentage of risk factors was higher in NSTEMI group and difference with UA was statistically significant (p <0.05). Serum BNP in UA 64.9±13.07 and in NSTEMI 107.2±11.53. The mean difference of serum BNP between two groups is statistically significant. In UA group the SYNTAX score was found 13.2±11.1 and in NSTEMI 19.9±13.5 which is statistically significant. In UA group maximum patients were found two vessel disease and in NSTEMI maximum patients in three vessel disease. 70.0% of patients of three vessel disease had e 80pg/ml of BNP. The association is statistically significant (p< 0.05). Higher the level of BNP reflect higher the vessel involvement and SYNTAX score irrespective of UA and NSTEMI. Conclusion: Our study reveals BNP is a candidate for entry into the setting of principal risk scores. Our findings indicate that the level of BNP may reflect the severity of ischemic insult even when irreversible injury and systolic dysfunction have not occurred. University Heart Journal Vol. 12, No. 1, January 2016; 17-22